Comparison of clinical examination & MRI against arthroscopy in diagnosis of Meniscal and anterior cruciate ligament injuries of knee joint - Mian Maqbool Hussain, Shafiq Ahmad, Usman Ahmad, Abdul Latif Shahid, Rana Dilawaiz Nadeem, Mumtaz Hussain, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: The most frequent internal instability of the knee is a meniscal tear. Most cost-effective and the primary diagnostic method is a physical examination of the knee joint. MRI is a non-invasive and extremely sensitive method of study and it frequently detects subtle and early alterations in the soft tissues. Arthroscopy is a highly specific and sensitive method which is useful for both diagnosis and treatment but it is an invasive treatment. Objective To assess the accuracy for clinical examination and arthroscopy to diagnose the anterior cruciate ligament and meniscal injuries in knee joint. To examine how accurate MRI is, as compared to arthroscopy in diagnosing anterior cruciate ligament and meniscal injuries in knee. Anassociation of diagnostic accuracy of MRI and clinical examination in diagnosis of anterior cruciate ligament and meniscal injuries in knee joint. Material and Methods: A Cross-sectional study conducted at Department of Orthopedic Surgery, Services Institute of Medical Sciences (SIMS). This study completed in one year and two months after the acceptance of synopsis. A sample of 120 patients was calculated for this study. A clinical diagnosis of meniscal, posterior cruciate ligament, anterior cruciate ligament, lateral collateral ligament, and medial collateral ligament injury of the knee has made after these patients gave their up-to-date consent. These patients were evaluated on the basis of MRI and Arthroscopy. We used SPSS to evaluate all data, with arthroscopy serving as the gold standard. Results: The study contained 120 patients. The mean age of these patients is between 30.8 ± 6.93 years. Most of the patients are male. The most common ligament involved in this study found to be ACL followed by medial Meniscal injury. Findings from clinical examination are correlated with Arthroscopic findings and it found more sensitive for ACL injuries (97.5%) while it is most specific for ACL as well as Medial Meniscal injuries (100%). Findings from MRI are also correlate with Arthroscopy, MRI found most sensitive to detect ACL injuries (95.8%) and it is most specific for ACL injuries also (100%). We also compare the MRI findings with clinical examination finding and found that, clinical examination is almost equally accurate as MRI to detect the injuries of ACL injuries with sensitivity of clinical examination 97.5% and MRI 95.8% and found 100% for ACL injuries. Conclusion: We concluded that the clinical examination is batter for diagnosing cruciate ligamentous injury while MRI is batter for diagnosis of meniscal injury, in case of knee injuries. So we may skip MRI for patients with cruciate injury &directly proceed towards arthroscopy. In difficult cases and the cases which are involving meniscal injury both MRI and arthroscopy may be considered.